MANAJEMEN KOMUNIKASI KRISIS PADA KAKU FOOD: STUDI KASUS PENANGANAN ULASAN NEGATIF DI MEDIA SOSIAL - Nasir, Nasir (STISIP Widyapuri Mandiri Sukabumi, 2025)
Kaku Food as a fast-growing culinary brand in Indonesia faces challenges in managing negative reviews on social media. Negative reviews can have an impact on the reputation and trust of consumers if not handled properly. This study aims to analyze the crisis communication management strategy implemented by Kaku Food in dealing with negative reviews on social media. The research method used is a case study with a qualitative approach. Data was collected through interviews with Kaku Food's communication team, analysis of social media content, and related documentation. The results of the study show that Kaku Food implements a crisis communication strategy based on quick response, openness, and a personal approach to consumers who give negative reviews. In addition, the company uses social media as the main channel in managing interactions with customers, providing clarification, and rebuilding the brand image. These findings show that responsive and transparent handling of negative reviews can mitigate adverse impacts on a company's reputation. The contribution of this research lies in further understanding the effectiveness of crisis communication strategies in the culinary industry, especially in the context of social media. The practical implications of this study can be a reference for culinary business actors in developing communication policies that are more adaptive to the dynamics of public opinion in the digital era.